Drafting an Army: The Playful Pastime of Warhammer 40, 000. (March 2014) - Carter, Marcus; Gibbs, Martin; Harrop, Mitchell
Multiple recent works have emphasized the contribution that nondigital game scholarship can make to the study of games and gameplay. Warhammer 40, 000 is the market dominator of the nondigital tabletop wargame genre. In this article, we perform a ludological analysis of the process of preparing, or drafting, an army for a competitive Warhammer 40, 000 tournament. We find that there are four interrelated categories of resources that influence this fundamentally playful process. Our results indicate that this process of preparation constitutes a core component of the appeal of Warhammer 40, 000. This emphasizes the importance of understanding the diverse activities that go into gameplay that often exceed the computer game "client" or board of play. We suggest the category of engagement pastime to encapsulate these extended, ongoing elements of Warhammer 40, 000's appeal, which we define as a collection of interlinked and associated activities that serve to occupy one's time and thoughts pleasantly .